Evaluasi Kinerja Sistem Informasi Manajemen Farmasi Di Rs Roemani Muhammadiyah Dengan Metode Hot Fit Model - Reni Murnita; Eko Sediyono; Cahya Tri Purnami (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Performance evaluation of Pharmacy Management Information System (PMIS) at Roemani Hospital was done because a policy of pharmacy system operation had not been fully implemented, a finance manager was difficult to predict expenditures to buy stock of medicines, information about amount of medicine on the pharmacy information system was different from amount of medicine which was available in repository, and quality of pharmacist was still low. Analysis model of HOT - Fit put important components on information system namely Human, Organization, and Technology. This research aimed to find out about performance of pharmacy information system at Muhammadiyah Roemani Hospital viewed from users’ perceptions using indicators of Hot Fit Model. This was descriptive research using quantitative approach. Population was all officers (40 persons) who were involved in PMIS. Research instruments consisted of a questionnaire, an observation sheet, and guidance interview. Furthermore, data were analyzed using descriptive statistics continued by categorizing to be good (e”mean/median) and bad (<mean/median) using data normality. The result of observation revealed that overall; viewed from total score of all aspects, mostly respondents had good performance of PMIS (75%). In addition, viewed from the aspects of human and organization, most of them had bad performances (55%) and (57.5%) respectively. In contrast, viewed from the aspect of technology, most of them had good performance (55%). As a conclusion, the performance of PMIS had been categorized as good. It had fulfilled the aspects of timeliness of receiving information and completion of the information. In addition, the aspects of information quality had fulfilled criteria of completeness and relevance but have not fulfilled accuracy of information. The aspect of technology was categorized as good performance whereas performances of the other aspects, namely human and organization were not good. These factors caused inaccuracy and quickness of providing information. As a suggestion, further pieces of follow- up research need to be conducted to examine recommendation (SOP of a pharmacist, SOP of a MIS officer, a training schedule, and master plan of pharmacy IS) which is provided to identify effects of a PMIS use. In addition, supervision by head of pharmacy needs to be done to monitor performance of pharmacist related to the implementation of SOP.